Behavioural changes and flight response of a mosquito (Culicidae) and an earthworm (Lumbricidae), respectively, after exposure to imidacloprid - Tsotesti, Palesa Andile Adrena (Ecotoxicology (London, England), 2022)
© 2021. The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.